Večkratni odstop terjatve - Juhart, Miha (Pravni letopis, 2012)
Multiple assignment of a claim (cessio) occurs if the assignor (transferor) transfers the same claim to several assignees (transferees). The law must determine who among several assignees in such a case acquires the claim against the debtor; that is, which of the assignments effects legal succession of the claim. Under the current Slovenian law, the precedence goes to the assignee that was first notified to the debtor by the assignor. This rule applies to contractual assignments and various forms of statutory assignments. A different rule applies to the assignment for collateral: in a conflict of several assignees, the one to whom the claim was first assigned intrust gains the precedence. The problem of multiple assignment can also arise in relationships containing an international element. In such relations, the law of the assignment contract applies, and not the debtor's law.
Keywords: cesija; dolgovi; terjatve; zavarovanje